Safety of Rimegepant, an Oral CGRP Receptor Antagonist, Plus CGRP Monoclonal Antibodies for Migraine. Issue 8 (16th August 2020) - Berman, Gary; Croop, Robert; Kudrow, David; Halverson, Philip; Lovegren, Meghan; Thiry, Alexandra C.; Conway, Charles M.; Coric, Vladimir; Lipton, Richard B.
Abstract : Objective: Evaluate the safety and tolerability of oral rimegepant when used for acute treatment concomitantly with a monoclonal antibody (mAb) targeting the calcitonin gene‐related peptide (CGRP) ligand or receptor (CGRP mAb) for the preventive treatment of migraine. Background: The efficacy of CGRP mAbs for the preventive treatment of migraine and the small molecule CGRP receptor antagonist rimegepant for acute treatment has been demonstrated in randomized controlled clinical trials. Over the past few years, the US Food and Drug Administration has approved 4 CGRP mAbs for the preventive treatment of migraine and 2 small molecule CGRP receptor antagonists for the acute treatment of migraine. A previous case report of 2 patients receiving concomitant treatment with rimegepant and erenumab suggested that rimegepant may be safely used as acute treatment in patients who are also receiving a preventive regimen involving CGRP mAbs. We report here 13 additional patients with migraine who simultaneously used rimegepant and either erenumab, fremanezumab, or galcanezumab and assess the rate of on‐treatment adverse events (AEs). Methods: This was a substudy nested within a multicenter, open‐label, long‐term safety study in adults with 2‐14 monthly migraine attacks of moderate to severe pain intensity. A subgroup experiencing 2‐8 monthly attacks and taking a stable dose of a CGRP mAb also took rimegepant 75 mg as needed up to once daily for acute treatment for 12 weeks. Results: The 13 patients (11 women [85%]; mean age 49.9 years) enrolled in the substudy were being treated with CGRP mAbs (erenumab [n = 7], fremanezumab [n = 4], or galcanezumab [n = 2]). Mean (SD) time in the rimegepant treatment period was 9.6 (4.6) weeks. Mean (SD) 4‐week rimegepant exposure was 7.8 (5.5) doses; a total of 224 doses were taken. Five (38%) patients reported ≥1 on‐treatment AE. Of these, 2 (15%) patients had mild or moderate nasopharyngitis; no other AEs occurred in ≥2 patients. Three patients had AEs of mild or moderate severity that were considered potentially treatment‐related. No patients had serious AEs, AEs leading to discontinuation, or aminotransferase levels >3× the upper limit of normal. Conclusion: Rimegepant, when used as an oral acute treatment in patients receiving CGRP mAbs as preventive treatment, was well tolerated; no safety issues were identified. Studies involving larger patient populations are needed to confirm these findings.